PROBLEMATIKA PENJATUHAN HUKUMAN PIDANA MAT - Muhammad Umpu Dilaga; Mitro Subroto (Universitas Muara Bungo, 2021)
The Constitutional Court's decision on the death penalty reinforces the existence of the death penalty in Indonesia, and it shows controversy in society. People who do not agree with the death penalty say that the death penalty is not in accordance with the protection of human rights as regulated explicitly in Article 28 A in conjunction with Article 28 I of the amendments to the Indonesian constitution. Including reneging on international treaties that prohibit the death penalty. The death penalty is not the main punishment but is an extraordinary punishment and is always subject to alternative punishments. The death penalty is the last resort, after failed human efforts, to protect society. In the national criminal law enforcement reform efforts in the future, the regulation on the death penalty will have significant friction.